Scientific substantiation and the release of saponins from plant raw material for food and cosmetic cream technology - N. Butova, Svetlana; A. Salnikova, Vera; A. Ivanova, Lyudmila; D. Schegoleva, Irina; A. Churmasova, Lyudmila (International Journal of Engineering and Technology, 2018)
The article presents the results of author scientific research dealing with the use of saponins, biologically active substances in food and cosmetics technology. The problems of their formation in plants, the chemical nature and the features are considered, biological and physico-chemical properties of saponins are studied. By their nature, saponins are divided into steroid and triterpene, differing by glycoside part of a molecule, thus, with different biological and chemical properties, but they are all capable to develop foam in aqueous solutions, and this feature is the origin of their name. The name originated from the word «Sapo», which means soap. It should be noted that at present saponins are not studied fully as other biologically active substances (BAS), although they are of interest and relevance. In the course of scientific work, about 20 species of saponin-containing plant material, both steroid and triterpene ones, were selected and analyzed for the determination of saponins. The selection of raw materials with the highest content was performed for their further use in cosmetics and as the surfactants in the production of emulsion food products. The following research methods were used in the work: qualitative reactions to the presence of saponins, foaming, saponin extraction, the release from dry aqueous extract of both steroid and triterpin ones. The method and the scheme of their release and precipitation are presented in the article.The work was carried out within the framework of the state assignment of FSBEI HE «Moscow State University of Food Production» No. 14.7404.2017/бч «Scientific and applied bases of application of traditional and nonconventional vegetable raw materials and secondary products of its processing (fruit and berry, grain, bean, oil, essential oil, herbs) in technology of specialized products of the food industry, cosmetology and pharmacy»